Las garantías preferidas en la regulación bancaria - Raygada Castillo, Miguel Angel (2023)
The preferred guarantees are one of the most important tools that Peruvian banking regulation must mitigate credit risk and strengthen the soundness of financial system institutions, reducing the probability of bankruptcies and f inancial crises. Its main function, in addition to supporting credits, is to mo tivate these entities to require their clients to provide this type of guarantee. This allows them to expand individual legal financing limits, while reducing the provisions needed in case borrowers see their credit rating diminished. This article dives into the underlying logic of preferred collateral regulation, exploring this concept in detail in the financial and legal spheres.